Science and education: modern trends - Lysenko E. M., Iantser O. V., Astafeva O. A., Koloskova T. A., Kapustina O. V., Shabaev V. G., Solovev V. V., Savinov A. M., Builova L. N., Builova L. N., Kargina Z. A., Karimova L. A., Komutstsi L. V., Sungatullina A. O., Shamtieva M. R., Badashkeev M. V., Sofronova N. I., Sofronov G. A., Bokova O. A., Volokhov S. P., Shamarina E. V., Zhdanova S. N., Dolgova V. M., Popova T. N., Maslennikova D. I., Pavlova V. S., Ermakova I. A., Gogolin V. A., Efremova L. I., Grigorash O. V., Efimova S. A., Kravec A. V., Zykov M. B., Kirpicheva M. A., Magomedova G. M., Skoblikova T. V., Skripleva E. V., Gorokhov V. F. (Science and education: modern trends, 2015)
The article deals with the main idea, basic definitions, foundations and technologic components of the gender in social and music education, the adaptation of boys and girls. The gender differences of boys and girls are proved on the conceptual, research and methodology level. The author comes to the conclusion about the opposing one another perception and absorption algorithms of boys (from the sense bearing to the emotional) and of girls (from the emotional to the sense bearing). The subject matter of the gender differentiation method is considered as an innovative method; research and methodology tips are given.
Keywords: гендерный подход; нейро‐психологические особенности девочек и мальчиков; метод гендерной дифференциации; gender approach; neuropsychological particularities of boys and girls; the gender differentiation method